AIDS, allergy, and rheumatology - Lane, Nancy E. (Allergy and immunology, 1997)
In Aids Allergy and Rheumatology, clinical experts survey the latest information available on the key rheumatic and allergic issues that physicians face in treating the HIV-infected patient. Their articles focus on the rheumatologic and dermatologic manifestations of HIV-1 infection, which include arthritis, myopathies, vasculitis, sicca syndrome, other autoimmune phenomena, and psoriasis. They also examine the question of allergic reactions in HIV patients, including drug hypersensitivity, with special attention given to adverse reactions to trimethoprim-sulfamethoxazole, the most frequently prescribed anti-infective. Practical advice for the diagnosis and treatment of these problems is given in full. Aids Allergy and Rheumatology offers physicians a comprehensive guide to the diagnosis and treatment of the allergic, immunologic, and rheumatic complications in HIV patients. Authoritative and practice-oriented, the book is destined to become a standard resource for all those treating AIDS patients today.